Multigenerational obesity-induced perturbations in oocyte-secreted factor signalling can be ameliorated by exercise and nicotinamide mononucleotide. Issue 3 (29th May 2018) - Bertoldo, M J; Uddin, G M; Youngson, N A; Agapiou, D; Walters, K A; Sinclair, D A; Morris, M J; Gilchrist, R B
Abstract: STUDY QUESTION: Can maternal and offspring high-fat diet (HFD)-induced changes in mRNA expression levels in mice be ameliorated by interventions in female offspring? SUMMARY ANSWER: Our results indicate that exercise and nicotinamide mononucleotide (NMN) can ameliorate the negative effects of maternal and post-weaning HFD in female offspring. WHAT IS KNOWN ALREADY: Maternal and post-weaning HFD can perturb offspring developmental trajectories. As rates of maternal obesity are rising globally, there is a need for effective treatments in offspring to ameliorate the negative effects from a maternal obesogenic environment. Modulation of the nicotinamide adenine dinucleotide (NAD + ) pathway by exercise and the NAD + precursor NMN has previously been shown to reduce the effects of obesity. STUDY DESIGN, SIZE, DURATION: This study consisted of a multigenerational study using C57Bl6 mice. Mice were fed a control (chow) or HFD ad libitum throughout mating, pregnancy and lactation ( n = 13–25). Female offspring ( n = 72) were then also supplied either a chow or HFD post-weaning. At 9 weeks of age offspring from HFD dams were subjected to exercise on a treadmill for 9 weeks or at 16 weeks of age administered NMN (i.p.) for 2.5 weeks. At 18.5 weeks mice were euthanized and ovaries and cumulus–oocyte complexes (COC) were collected to examine the possibility of ameliorating the negative effects of maternal and post-weaning HFD. PARTICIPANTS/MATERIALS, SETTING, METHODS: Ovary and COC mRNA expression was analysed using RT-qPCR. An initial screen of candidate genes was developed to test which molecular pathways may be involved in generating adverse reproductive system effects. For histological analysis, ovarian tissue was fixed in paraformaldehyde and embedded in paraffin and stained with haematoxylin and eosin. The numbers of primordial, primary, secondary and antral follicles were counted. MAIN RESULTS AND THE ROLE OF CHANCE: In the offspring's COC, maternal obesity increased both growth differentiation factor 9 ( Gdf9: 2-fold; P < 0.05, HFD versus chow) and bone morphogenetic protein 15 ( Bmp15: 4-fold; P < 0.05, HFD versus chow) mRNA expression levels while exercise and NMN interventions did not regulate Gdf9 and Bmp15 in the same manner. In whole ovary, maternal diet programmed a 25–50% reduction in FSH receptor and sirtuin-3 mRNA expression levels in daughter ovaries ( P < 0.05, HFD versus chow). There was a significant interaction between HFD and intervention on the proportion of large preantral and preovulatory follicles ( P < 0.05). However, the increase in preovulatory follicles did not translate to increased oocyte yield. NMN administration resulted in reduced body weight in HFD-fed individuals. LIMITATIONS, REASONS FOR CAUTION: It is unclear if the changes in oocyte mRNA expression levels reported here will impact oocyte quality and fertility in offspring. Offspring ovulation rate or fecundity could not be studied here and fertility trials are required to determine if the changes in gene expression do reduce fertility. WIDER IMPLICATIONS OF THE FINDINGS: Our results demonstrate that maternal and offspring HFD perturbs key signalling pathways that are known to regulate fertility in mice, highlighting the importance of interventions in helping to prevent the declining rates of fertility in the context of the current obesity epidemic. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by grants and fellowships from the National Health and Medical Research Council to R.B.G. (APP1023210, APP1062762, APP1117538) and to M.J.M. and D.A.S. (APP1044295). DAS is a consultant to and inventor on patents licenced to Ovascience, Metrobiotech and GlaxoSmithKline. The other authors declare that there is no conflict of interest.